Dispersal of diapausing Tetranychus urticae and T. kanzawai. Issue 2 (9th August 2016) - Ghazy, Noureldin Abuelfadl; Otsuki, Hatsune; Sekido, Tomoe; Yano, Shuichi; Amano, Hiroshi
Abstract: The spider mites Tetranychus urticae Koch and Tetranychus kanzawai Kishida (Acari: Tetranychidae) overwinter mostly as mated adult diapausing females. Their overwintering survival depends in part on their dispersal towards suitable habitats. We investigated the dispersal behaviour of diapausing females of T. urticae and T. kanzawai with respect to factors known to affect the dispersal of non‐diapausing mites: light, population density, gravity, and humidity. In general, diapausing females of T. urticae showed a stronger tendency to disperse than did those of T. kanzawai under all test conditions. High population density promoted the dispersal of diapausing T. urticae, but not of T. kanzawai . Dispersal of diapausing females of both species was not significantly affected by gravity, humidity, or whether feeding damage was caused by conspecifics or heterospecifics. On plants, more T. urticae than T. kanzawai moved downward. We propose that dispersal after the onset of diapause may be an important life‐history strategy in T. urticae, but not in T. kanzawai .